2013
DOI: 10.5114/fn.2013.34193
|View full text |Cite
|
Sign up to set email alerts
|

Original article Loss of genetic material within 1p and 19q chromosomal arms in low grade gliomas of central nervous system

Abstract: Loss of genetic material within 1p and 19q chromosomal arms in low grade gliomas of central nervous system D Da an ni ie el l R Rę ęc cł ła aw wo ow wi ic cz z 1 1 , , M Mi ir ro os sł ła aw w S St te em mp pn ni ie ew wi ic cz z 1 1 , , W Wo oj jc ci ie ec ch h B Bi ie er rn na at t 2 2 , , J Ja an nu us sz z L Li im mo on n 3 3 , , P Pa aw we eł ł S Sł ło on ni ie ew ws sk ki i IntroductionThe definition of low grade glioma encompasses three types of WHO grade II tumours including: diffuse astrocytoma (DA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
2
1
1
Order By: Relevance
“…With respect to 1p19q deletion status, overall survival was improved but was not significantly different [22]. Despite previous studies that indicate that median survival in patients with diagnosed 1p and 19q deletion is twice as long in comparison with patients in whom no deletion was observed, our study did not find such a significant difference [11].…”
Section: Discussioncontrasting
confidence: 56%
“…With respect to 1p19q deletion status, overall survival was improved but was not significantly different [22]. Despite previous studies that indicate that median survival in patients with diagnosed 1p and 19q deletion is twice as long in comparison with patients in whom no deletion was observed, our study did not find such a significant difference [11].…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, Smith et al [21] have demonstrated that the association of 1p and 19q loss with prolonged survival is also evident in low-grade oligodendroglioma patients and that this association may be independent of PCV chemotherapy. Ręcławowicz1 et al [22] in his study proved that combined loss involving chromosomes 1p and 19q is a strong factor for better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Олигодендроглиальные опухоли (ОДО) считаются более благоприятными, чем астроцитарные, особенно при наличии характерной для ОДО транслокации 1p19q: медиана ОВ больных с ГНСЗ при наличии данной мутации вдвое выше, чем при ее отсутствии (80 мес против 41 мес) [6]. В свою очередь ДА, самая частая опухоль ВОЗ grade II, делится на несколько гистологических подтипов: фибриллярная астроцитома встречается у 65,2% больных, протоплазматическая -у 5,8% и гемистоцитарная -у 29%.…”
Section: морфологическое строение опухолиunclassified